1999
DOI: 10.1159/000045320
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Analysis of the Carboxy Terminus of the Beta and Gamma Subunits of the Epithelial Sodium Channel in Patients with End-Stage Renal Disease

Abstract: Background: Mutations in the carboxy termini of the beta subunit (hβENaC) and the gamma subunit (hγENaC) of the human epithelial sodium channel have been identified in patients with Liddle syndrome. Moreover polymorphisms have been described in these genes, the clinical relevance of which for progression to end-stage renal disease (ESRD) is unknown. We, therefore, have screened ESRD patients for putative variants of these genes. Methods: We investigated 256 chronic hemodialysis patients, including 123 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1999
1999
2004
2004

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Several previous studies examined partial sequences of ␤and ␥subunits (only selected exons in the carboxyl-terminal region) (35)(36)(37) in hypertensive subjects. Although Persu et al (35) identified novel rare SNPs, no mutation was found to be definitively associated with hypertension (35)(36)(37). Exons 8 and 12, noted in a previous study (35), are here numbered 9 and 13, as we now know that there are 13 exons in the ␤ ENaC gene (9), not 12.…”
Section: Sequence Variants In Genes Encoding Enac Subunitsmentioning
confidence: 99%
“…Several previous studies examined partial sequences of ␤and ␥subunits (only selected exons in the carboxyl-terminal region) (35)(36)(37) in hypertensive subjects. Although Persu et al (35) identified novel rare SNPs, no mutation was found to be definitively associated with hypertension (35)(36)(37). Exons 8 and 12, noted in a previous study (35), are here numbered 9 and 13, as we now know that there are 13 exons in the ␤ ENaC gene (9), not 12.…”
Section: Sequence Variants In Genes Encoding Enac Subunitsmentioning
confidence: 99%
“…Thus, mutations in these genes may not be associated with the disease [46]. One has to take into consideration, however, that the search was often restricted to the cytoplasmic carboxy-terminal domain of the SCNN1 genes.…”
Section: The Epithelial Sodium Channel and Its Implication In Essentimentioning
confidence: 99%